Perinatal Resilience for the First 1,000 Days of Life. Concept Analysis and Delphi Survey - Van Haeken, Sarah; Braeken, Marijke A. K. A.; Nuyts, Tinne; Franck, Erik; Timmermans, Olaf; Bogaerts, Annick (Frontiers in Psychology, 2020)
Background: The ability to cope with challenges and stress in life is generally understood as resilience. Pregnancy and parenthood are challenging times. The concept of resilience is receiving increasing interest from researchers, clinicians, and policy staff because of its potential impact on health, wellbeing, and quality of life. Nevertheless, the concept is less studied during the perinatal period. Objectives: The aim of this study is to understand the concept of perinatal resilience, including the underlying processes, more specifically during the first 1000 days of life. Methods: A concept analysis according to the Walker and Avant (2011) framework was used, to investigate the basic elements of the concept. Concurrently, a two-round Delphi survey involving researchers, clinicians, epidemiologists, mothers and fathers (N=21), was conducted to prioritize the terms associated with perinatal resilience. Data collection took place between January and April 2019. Results: Through concept analysis and Delphi survey, five defining attributes for perinatal resilience were identified: social support, self-efficacy, self-esteem, sense of mastery and personality. Additional terms, rated important by the Delphi survey, were linked to the consequences of being resilient during the perinatal period for the individual and his/her family. Specifically, families experience personal growth and achieve family balance, adaptation or acceptance. Conclusions: Based on the results of the concept analysis and Delphi survey, we describe perinatal resilience as an iterative process towards a greater wellbeing in the form of personal growth, family balance, adaptation or acceptance, when faced with stressors, challenges or adversity during the perinatal period. The presence of resiliency attributes such as social support, sense of mastery, self-efficacy and self-esteem enhance the capacity to be resilient and probably prevent mental health problems.